Serum calcium and phosphorus levels in patients of HIV positive under the treatment - Asha Kiran, N; Ravi Kanth, M; Satyannarayana, V A R; S Girish Kumar, P (International journal of clinical biochemistry and research, 2020)
The abnormal levels of serum calcium and phosphorus are mostly seen in diseases of bone, kidney, tuberculosis, parathyroid diseases etc. The present study is aimed to measure the serum total calcium and phosphorous levels in HIV infected patients and in healthy controls. This cross sectional case-control study was conducted at Department of Biochemistry, NRI Medical College and General Hospital, Chinnakakani, Guntur, AndhraPradesh. A total of 90 HIV positive patients were taken as cases and 90 healthy subjects served as controls. Patients with congestive heart failure, liver diseases, diabetes and hypertension were excluded from the study. Seropositivity of all 90 HIV patients was confirmed by HIV TRI-DOT test. 5 ml of venous blood sample was collected after taking aseptic precautions from the study subjects. Serum was used for theestimation of Calciumby O-Cresolphthalein complexone method and Phosphorus by Fiske and Subbarow Method. In this study, HIV positive patients had significantly reduced mean serum calcium (8.02±0.86 mg/dl) and phosphorous (2.68±0.65 mg/dl) levels compared with healthy subjects. The present study may conclude that serum levels of calcium and phosphorus were decreased in HIV positive patients, suggesting that the levels of calcium and phosphorous should be closely monitored.